CTH/MPST double ablation results in enhanced vasorelaxation and reduced blood pressure via upregulation of the eNOS/sGC pathway - Katsouda, Antonia; Markou, Maria; Zampas, Paraskevas; Varela, Aimilia; Davos, Constantinos H.; Vellecco, Valentina; Cirino, Giuseppe; Bucci, Mariarosaria; Papapetropoulos, Andreas (Frontiers in Pharmacology, 2023)
Hydrogen sulfide (H2S), a gasotransmitter with protective effects in the cardiovascular system, is endogenously generated by three main enzymatic pathways: cystathionine gamma lyase (CTH), cystathionine beta synthase (CBS) and 3-mercaptopyruvate sulfurtransferase (MPST) enzymes. CTH and MPST are the predominant sources of H2S in the heart and blood vessels, exhibiting distinct effects in the cardiovascular system. To better understand the impact of H2S in cardiovascular homeostasis, we generated a double Cth/Mpst knockout (Cth/Mpst-/) mouse and characterized its phenotype. CTH/MPST-deficient mice were viable, fertile and exhibited no gross abnormalities. Lack of both CTH and MPST did not affect the levels of CBS and H2S-degrading enzymes in the heart and the aorta. Cth/Mpst-/- mice also exhibited reduced systolic, diastolic and mean arterial blood pressure, and presented normal left ventricular structure and fraction. Aortic ring relaxation in response to exogenously applied H2S was similar between the two genotypes. Interestingly, an enhanced endothelium-dependent relaxation to acetylcholine was observed in mice in which both enzymes were deleted. This paradoxical change was associated with upregulated levels of endothelial nitric oxide synthase (eNOS) and soluble guanylate cyclase (sGC) α1 and β1 subunits and increased NO-donor-induced vasorelaxation. Administration of a NOS-inhibitor, increased mean arterial blood pressure to a similar extend in wild-type and Cth/Mpst-/- mice. We conclude that chronic elimination of the two major H2S sources in the cardiovascular system, leads to an adaptive upregulation of eNOS/sGC signaling, revealing novel ways through which H2S affects the NO/cGMP pathway.